Killoe - L'Amour, Louis (London Bantam Books, 1979)
For Dan Killoe, leading a cattle drive across harsh wilderness newly won in the war with Mexico meant a chance to prove himself to his father and his friends. It also meant riding alongside the man who had been like an older brother to him, a charismatic gunman named Tap Henry. But there was a lot about Tap that Dan didn't know. Through miles of dust, nights under the stars, and a battle with Comanches, they would ride together, until Tap revealed a side of himself Dan had never seen before. And when Tap disappears with the woman Dan loves, a deadly drama unfolds in which loyalties are shattered and the line between friend and enemy is violently crossed.
Keywords: Western stories -- Cattle drives -- Friendship